Effect of soybean plant density on stem blight incidence - Farias,Monica (2019)
ABSTRACT No-till system and high plant density are common practices in soybean crops of the Brazilian southern region, which has increased the incidence of stem and pod diseases. The objective of this study was to evaluate the effect of plant populations on stem blight incidence. The experiments were conducted in Muitos Capões Municipality, Rio Grande do Sul State, during the seasons 2006/07 and 2007/08, using cultivars BRS 255 RR and CD 213 RR. The evaluated populations had 12, 18, 24, 30 and 36 plants m-2, spaced 0.45 m between rows. The experimental plot units consisted of 5m width and 10m length, arranged in randomized blocks with four replicates. Stem blight incidence was quantified at phenological stages R5.1, R5.5, R6 and R7 and the collected data underwent regression analysis. Higher soybean plant densities caused a positive and significant increase on stem blight incidence in all four phenological stages for both cultivars and seasons. There was no significant difference for soybean grain yield according to the increase in plant population. Results indicated that soybean management preventing high plant densities can contribute to reduce stem blight incidence.